Program Pegasuhan Kyai Dalam Membangun Karakter Di Pondok Pesantren La Tansa Parakan Santri Lebak - Solihin (LPPM STAI La Tansa Mashiro, 2024)
The parenting patterns of kyai in an Islamic boarding school determine the formation of students with character, supported by programs to support parenting. The aim of this research is to determine the parenting patterns applied by kyai and parenting programs in efforts to build the character of students in Islamic boarding schools. The research results show that the kyai's parenting pattern in building character at the La Tansa Mashiro Lebak Islamic boarding school is very good, supported by disciplinary programs for independent living, compliance with boarding school regulations, formal activities, extracurricular activities that support the formation of students with character. In conducting research, researchers saw directly the conditions in the field being studied, with responses and participation from the Islamic Boarding School.